Designing a Quality Improvement Program With Electronic Health Records: New York City's Health eQuits. (March 2015) - Duquaine, Damon; Farley, Shannon M.; Sacks, Rachel; Mandel-Ricci, Jenna; Silfen, Sheryl L.; Shih, Sarah C.
Despite clear recommendations for identifying and intervening with smokers, clinical preventive practice is inconsistent in primary care. Use of electronic health records could facilitate improvement. Community health centers treating low-income and Medicaid recipients with greater smoking prevalence than the general population were recruited for a pilot program. Key design elements used to engage centers' participation include designating a project champion at each organization, confirming ability to transmit data for reporting and participation, and offering money to facilitate initial engagement; however, financial incentives did not motivate all organizations. Other methods to elicit participation and to motivate practice change included building on centers' previous experiences with similar programs, utilizing existing relationships with state cessation centers, and harnessing the "competitive" spirit—sharing both good news and areas for improvement to stimulate action. These experiences and observations may assist others in designing programs to improve clinical interventions with smokers.